Pengaruh Pijat I Love You (ILU) terhadap Rehabilitasi Fungsi Pencernaan Anak Pascaoperasi Perut - Yuli Lestari; Nova Nurwindasari (Jurnal Kesehatan, 2020)
Recovery normal digestive function in postoperative abdominal patients requires a process of stages in the recovery period, phenomena in postoperative ileus are commonly found ileus in postoperative patients. Ileus or digestive peristalsis failure due to postoperative mechanical and non-mechanical factors of the abdomen, generally there are also include symptoms of abdominal distension and peristalsis. Providing complementary nursing care with the I Love You (ILU) massage method can help postoperative digestive stomach rehabilitation quickly. This study aims to identify the effect of I Love You (ILU) massage on the rehabilitation of digestive function postoperative stomach in RSUD Hi. Dr. Abdul Moeloek Lampung Province. The study used a quasi-experimental design, with a pre-post test design approach. The total sample of 32 respondents selected using nonprobability sampling with consecutive sampling techniques. The results showed the mean intestinal noise before ILU massage was 4.19; the estimated 95% interval result is believed that the mean bowel noise before intervention is 2.05 to 6.33 times. The mean intestinal noise after ILU massage was 4.88; the estimated 95% interval result is believed that the average bowel noise after the intervention is 2.54 to 7.21 times. Statistical test results showed that there were significant differences between bowel sounds before and after I Love You (ILU) massage (p-value=0.016). Complimentary massage therapy I Love You (ILU) can be a choice of intervention that can help the recovery process of the digestive function of postoperative stomach patients.